"Nightown", "Necropolis", "Jerusalem" : les figures de la ville dans Ulysses de James Joyce - Philippe Birgy (Anglophonia)
This paper proposes to inquire into the textual functions played by the city of Dublin in James Joyce's Ulysses. Leaving aside the questions of the town-like or maze-like structure of the text itself and the hieroglyphic tracery of the flâneur's path—for these aspects have already been amply documented by Joycean scholars—it concentrates on the communal dimension that underlies Joyce's writing and on the stylistic inscription of a democracy to come that reaches beyond nationalism and citizenship (the latter being comically presented as Bloom's celestial Jerusalem). It also considers the town's monumental and paralyzing forces, but without opposing them squarely to the transience and mobility of literary signs.